Analysis Of Human Resources In Elementary School Using The Stages Of Patton Analysis - Djamal Said Askar; Muhammad Nasri Dini; Isnaeni Sofiana (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
AbstractPolicy analysis is a scientific discipline that uses rational argumentation by using existing data to assess, explain and generate ideas in order to solve a problem. This research will analyze education policy related to human resource management in elementary schools. This research was conducted at SD Muhammadiyah Imam Syuhodo Sukoharjo. The research method used is qualitative. The subject of this research is the principal of SD Muhammadiyah Imam Syuhodo. Data collection in this study used interview, observation, and documentation techniques. The data obtained were then analyzed by data reduction techniques, data presentation, and data verification. The results of this study indicate that there are HR problems at SD Muhammadiyah Imam Syuhodo, where there are still many teachers who have not graduated from S1. Among the policy solutions offered are: tightening the teacher recruitment process and requiring teachers to attend undergraduate courses.Keywords: Analysis, Human Resources, Elementary School